Efficacy of pretomanid-containing regiments for drug-resistant tuberculosis: A systematic review and meta-analysis of clinical trials - Simanjuntak, Arya M.; Daenansya, Raehan; Afladhanti, Putri M.; Yovi, Indra; Suyanto, Suyanto; Anggraini, Dewi; Rosdiana, Dani (Narra Sains Indonesia, 2023)
Concerns regarding the rise of drug-resistant tuberculosis (DR-TB) infections and the need for new drugs with shorter treatment time and fewer side effects have been voiced by the World Health Organization (WHO). The WHO revised its guideline to treat multi-drug resistant tuberculosis (MDR-TB) with a 6-month course of BPaLM (bedaquiline, pretomanid, linezolid and moxifloxacin) in 2022. However, a thorough study and meta-analysis of available evidence is required due to the limited confidence of the evidence confirming the effectiveness of pretomanid-containing regiments. The aim of this systematic review and meta-analysis was to evaluate the effectiveness of pretomanid-containing regiments in treating DR-TB patients. Data from six search engines were searched using inclusion criteria based on the PICOS framework. The keywords of pretomanid and tuberculosis or their alternatives were used. Using RoB2 Cochrane risk-of-bias tool for randomized clinical trials, data were independently extracted and the quality of the data was evaluated. Odds ratio (OR) and heterogeneity tests were used and the findings were presented in ORs and forest plots. A total of four studies with 237 patients was included in the final analysis and 204 (86%) patients had favorable outcome (cured) and 33 (14%) was not cured. Pretomanid-containing regimen (OR: 46.73; 95%CI: 11.76–185.7) and BPaLM/BPaL (OR: 41.67; 95%CI: 8.86–196.73) regimens were associated with favorable outcome (cured). This meta-analysis indicates that the pretomanid-containing regimen and the BPaLM/BPaL regimen could increase the chance to have favorable outcome in DR-TB patients.